Guided Inquiry Collaborative Learning (GICL) for Online Teaching in Cybersecurity: Challenges and Recommendations (Journal of The Colloquium for Information Systems Security Education, 2022)
The COVID-19 pandemic has required many educators to offer online courses. Given the evidence of the effectiveness of the Process-Oriented Guided Inquiry Learning (POGIL), many educators are interested in implementing POGIL in online environments. This paper first discusses the challenges of using the POGIL approach to teach courses. Then we share our experience and our proposed approach (GICL) for teaching cybersecurity topics via the Zoom platform in the online environment. Recommendations for overcoming some of these challenges for online teaching are provided.
Keywords: collaborative learning; online learning; POGIL; Process-Oriented Guided Inquiry Learning; Guided Inquiry Collaborative Learning